Mam' Lyddy's Recognition : 1908 - Page, Thomas Nelson, 1853-1922 (Salt Lake City, UT : Project Gutenberg, 2007)
"Mam' Lyddy's Recognition" by Thomas Nelson Page is a fictional narrative written in the early 20th century. As a work set in Southern society during the post-Civil War period, it explores themes of race, identity, and social hierarchy. The book likely addresses the complexities of the relationship between African American citizens and their former masters, encapsulated in the character of Mam' Lyddy, a former slave who navigates her place in a changing social landscape. The story centers on Mam' Lyddy, a strong and dignified figure who was a caretaker for the French family and a significant presence in their lives. As the narrative unfolds, she grapples with issues of respect and recognition after she moves to a new environment with her former master's family, the Graemes. Upon encountering the challenges of the Northern society, she confronts the changes in servant dynamics and asserts her identity against emerging social norms. Mam' Lyddy$1 (Bs journey reflects her struggle for dignity amidst social changes, her interactions with the Reverend Amos Johnson, and her ultimate desire for acknowledgment as an integral member of society. The plot underscores the themes of loyalty, exploitation, and the pursuit of self-worth, as seen through the lens of a woman who transcends her previous roles while demanding her rightful recognition. (This is an automatically generated summary.)s
Release date is 2007-11-16
Produced by David Widger
Keywords: Short stories; African Americans -- Fiction; Southern States -- Social life and customs -- Fiction